Calibration of the Tranus land use module: Optimisation-based algorithms, their validation, and parameter selection by statistical model selection. (September 2019) - Capelle, Thomas; Sturm, Peter; Vidard, Arthur; Morton, Brian J.
Abstract: Instantiating land use and transport integrated models (LUTI modelling) is a complicated task, requiring substantial data collection, parameter estimation and expert analysis. In this work, we present a partial effort towards the automation of the calibration of Tranus, one of the most popular LUTI models. First, we give a detailed mathematical description of the activity module and the usual calibration approach. Secondly, we reformulate the estimation of the endogenous parameters called shadow prices as an optimisation problem. We also propose an optimisation algorithm for the calibration of the substitution submodel, setting a base for future fully integrated calibration. We analyse the case of transportable and non-transportable economic sectors and propose a detailed mathematical scheme for each case. We also discuss how to validate calibration results and propose to use synthetic data generated from real world problems in order to assess convergence properties and accuracy of calibration methods. Results of this methodology are presented for realistic scenarios. Finally, we propose a model selection scheme to reduce the number of shadow prices that need to be calibrated, with the aim of reducing the risk of overfitting to data. Highlights: This work is a partial effort towards automatic calibration of Tranus. Reformulation of Tranus "shadow price" estimation as an optimisation problem An integrated optimisation algorithm for the calibration of the substitution submodel is proposed, with real case application. Validation and calibration are discussed, new synthetic scenario methodology is proposed. We propose a model selection scheme, aiming at a compromise between model complexity and goodness of fit to observations.